Pengaruh Perceived Support, Fear Of Failure Dan Self-Efficacy Terhadap Niat Berwirausaha Pada Mahasiswa S1 Manajemen Fakultas Ekonomi Dan Bisnis Universitas Airlangga - Jovi Sulistiawan (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2016)
The imbalance between job seekers and job opportunities cause an increase of unemployment rate in Indonesia. Thus make Universities try to increase entrepreneurship intention among students. Universities try to give support such as giving entrepreneurship education to students. This research examines whether entrepreneurship education has positive effects on entrepreneurial intention. Besides, this research examines whether attitudes towards entrepreneurship, perceived support and also fear of failure have effects on entrepreneurial intention among students. The data was collected using questionnaire instrument obtained from 254 respondents of Students of Management, Faculty of Economics and Business Airlangga University in Surabaya. The results of this study are expected to give some input for the University to increase the entrepreneurial intention among students.